2020
DOI: 10.15694/mep.2020.000135.1
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning team-based learning facilitation for an online platform to deliver preclinical curriculum: A response to the COVID-19 pandemic

Abstract: Due to the increasing number of COVID-19 cases globally, and the need for critical containment, Duke-NUS Medical School, Singapore, moved all of its preclinical classes online, keeping with national and university guidelines. The sudden move from face-to-face to online learning posed several challenges to the school's teambased learning (TBL) pedagogy. In TBL, student engagement is key to promote peer-to-peer learning. The educational faculty found that it was challenging to ensure student engagement through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…Furthermore, academic teacher guidance regarding expectations of interacting and engaging in online learning were perceived to be useful (Mukhtar et al, 2020). These findings support existing literature that highlight the importance of online learning that is structured, yet provides opportunities for interaction to promote student selfregulation (Keis et al, 2017;Mukhtar et al, 2020) and satisfaction with learning (Wong et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, academic teacher guidance regarding expectations of interacting and engaging in online learning were perceived to be useful (Mukhtar et al, 2020). These findings support existing literature that highlight the importance of online learning that is structured, yet provides opportunities for interaction to promote student selfregulation (Keis et al, 2017;Mukhtar et al, 2020) and satisfaction with learning (Wong et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…Further concerns for student welfare were raised by Smyth and colleagues (2012) who reported that poor communication between academic teachers and health professional students in online learning created feelings of frustration and anxiety. Health professional students have reported feelings of isolation from their peers and teachers when learning fully online (Wong et al, 2020), potentially impacting their general well-being (Kaup, et al, 2020). These negative experiences associated with online learning may not only impede students' motivation and learning but also may fail to meet their needs and expectations in preparation for healthcare delivery (Regmi & Jones, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In online TBL, the role of the facilitator took on a different form from face-to-face TBL [12][13][14]. In brief, the facilitator ensured that all the participants were muted throughout the session and that only one person speaks at any one time.…”
Section: Transitioning Teamlead From Face-to-face To Online In 2020mentioning
confidence: 99%
“…Prior to the classes, the administrative team was responsible for maintaining the online learning resources and granting access for all participants. They were also responsible for conducting training sessions for students and faculty on how to use the various online platforms and helping users to resolve technological problems in real time [14]. For example, they worked with hospitalbased faculty to overcome the poor Wi-Fi access in their institutions.…”
Section: The Education Administrative Team Played a Crucial Role In Implementing Online Tbl In 2020mentioning
confidence: 99%
“…Almost all articles referred to students having to rely more on online learning methods, which was more socially isolating. This seems to be more straight-forward for more didactic methods, as lectures are relatively easy to broadcast and team-based learning can take place in online 'rooms' (Wong et al, 2020). Clinical teaching is much harder to adapt due to safety and narrower clinical workload.…”
Section: Resultsmentioning
confidence: 99%